STUDI PERSEPSI KEPEMIMPINAN YANG POSITIF, KEPEMIMPINAN YANG MENDUKUNG, PERSEPSI KARYAWAN YANG POSITIF DAN BERPENGARUH TERHADAP PRODUKTIVITAS SUMBER DAYA MANUSIA PADA KARYAWAN PT.WAHANA KASIH MULIA - Didik Subiyanto; Jajuk Herawati; Ade Tursino (Among Makarti, STIE AMA Salatiga, 2021)
ABSTRACTThis study aims to analyze the influence of positive perceptions of leadership, supportiveleadership, positive employee perceptions and affect HR productivity. The sample of thisresearch is employees who work at PT.WAHANA KASIH MULIA. The method in this studyusing the Accidental Sampling method. This research is a quantitative research, thesample in this study is 100 employees. The results showed that employee perceptions hada positive and significant effect on positive employee perceptions, supportive leadershiphad a positive and significant effect on positive employee perceptions, employeeperceptions had a positive and significant effect on HR productivity, positive leadershipperceptions had no positive and significant effect. Human resource productivity issignificant, supportive leadership has a positive and significant effect on HR productivity,positive employee perceptions of HR productivity with positive employee perceptions asan intervention variable have a positive and significant effect and leadership supports HRproductivity with positive employee perceptions as a variable which has no positive andsignificant effect on the employees of PT.WAHANA KASIH MULIA.